Preparation of Crackers by Mixing of Cassava, Carrot, and Protein Isolated from Waste of Ketchup Factory with CaSO4 Ions - Lenny, Sovia (Talenta Publisher, 2022)
This research is one of the diversification efforts of food substances to create economically valuable nutritious food. It has been researched the use of isolation of protein from the waste of the Ketchup Industry as the mixture of crackers with various comparisons between isolating of the waste of protein from Ketchup Industry and cassava by adding an extract of carrot about its nutrient content also. The analyzing nutrient is protein content by using the Kjeldahl method and turning to dust β – carotene using the spectrophotometer and organoleptic test about the taste of crackers using a hedonic scale. The highest protein content and β – carotene is found in the crackers in comparison (1:6:3) namely 5,38 % and 53,59 ppm. Moreover, the lowest protein content and β – carotene is found in the crackers in comparison (1:0:0) namely 2.35 % and 27.49 ppm. The most delicious, crispy, and the most people like is the crackers with comparison (1:4:2).